HLA typing in Taiwanese patients with oral squamous cell carcinoma - Chia-Chun Lu; Tréjaut John; Chieh-Yuan Cheng; Chu-Sheng Lin; Chung-Ji Liu (Elsevier, 2014)
Background/purpose: The human leukocyte antigen (HLA) system, which plays a vital role in immunity, is the most polymorphic gene complex found in the human genome. This study investigated HLA-related alleles and haplotypes in Taiwanese patients with oral squamous cell carcinoma (OSCC). Materials and methods: HLA class I (HLA-A and HLA-B) antigens and class II (HLA-DRB1) alleles were determined in 105 patients with OSCC and compared with those in 190 healthy controls. The antigens were measured serologically and the alleles by sequencing-based typing. Results: Compared with the control group, patients with OSCC had higher frequencies of HLA-A24, HLA-B54, HLA-DRB1*0405, and HLA-DRB1*1201, while they had lower frequencies of HLA-B58 and HLA-DRB1*1302. Haplotype frequencies also varied significantly in individuals with OSCC, with certain haplotypes associated with lymph node metastases or a particular tumor stage. Conclusion: These results suggest that HLA genetic factors influence susceptibility to OSCC and perhaps to lymph node metastasis and tumor progression.